The Effect of Perceptual Deprivation on the Human EEG - Tait, Andrews Gordon (My University, 1977)
The slowing of the alpha rhythm of the EEG during perceptual deprivation was investigated to test John Zubek's hypothesis that the time course of the slowing was influenced by the length of the deprivation period; to provide a more comprehensive description of the EEG changes produced by the deprivation procedure using computer power spectral analysis of the EEG, and to discover the effect of deprivation on the other rhythms of the EEG, chiefly the 12-14 Hz. sleep spindles since their mechanism of generation is reasonably well understood and it has been suggested that the alpha rhythm is generated in a similar manner.
The experimental subjects (eight adult humans) were divided into two groups of four, one group undergoing four days and the other seven days of perceptual deprivation. Two control groups of two subjects each experienced either four or seven days of confinement. All subjects slept in the laboratory for three nights before and three nights after the deprivation period. The EEG was recorded polygraphically throughout the deprivation period, while samples of EEG for computer analysis were recorded on magnetic tape at regular intervals throughout each day.
The power spectral analysis of the EEG enabled us to provide a good quantitative description of several characteristics of the normal human EEG which were previously unknown or inadequately described. We found that all subjects showed a regular circadian variation in alpha frequency with the lowest values occurring in the early morning and the highest values occurring in the afternoon or evening. Three subjects showed bimodal distributions of power in the alpha range, indicating two distinct frequencies of alpha. The slower alpha was more prominent in frontal regions while the faster alpha was more prominent in occipital regions. Two subjects possessed high amplitude alpha in the occipital region during Stage 1 REM sleep. This alpha was about 1 Hz. slower than the occipital alpha during the walking state. The slower frontal and REM alpha rhythms also showed a circadian variation in frequency. Three subjects showed a different frequency of alpha when the eyes were open than when the eyes were closed. Sleep spindles showed a bimodal power distribution, the slower frequency spindle occurring only in the frontal area while the higher frequency spindle was prominent in the frontal and parietal regions.
The alpha frequency of the deprivation subjects decreased by 1.5 to 2 Hz. while the control subjects showed little or no change in alpha frequency. The time-course of the decrease in alpha frequency was similar in the four and seven day deprivation subjects, disconfirming Zubek's hypothesis that the seven day group would show a more gradual slowing. Subjects with high amplitude alpha showed a decrease in alpha amplitude while subjects with low amplitude alpha showed no change or an increase in alpha amplitude over the deprivation period. The low frequency frontal alpha was also showed during deprivation but showed no reduction in power. The theta rhythm showed some increase in power but no change in frequency over deprivation in two of the four subjects who showed measurable amount of this activity. The REM alpha was slowed to the same degree as the waking alpha remaining 1 Hz. slower throughout the deprivation period. In contrast, the frequency and amplitude of the sleep spindles were unaffected by the deprivation procedure and there appeared to be no regular circadian variation in spindle frequency. This suggests that current assumptions that alpha and spindles share a common mechanism may not be valid.
Keywords: Psychology; Psychology